HUBUNGAN ANTARA PERSEPSI TERHADAP KEMAMPUAN MATEMATIKA ANAK DENGAN SIKAP TERHADAP PROGRAM â€I MATHSâ€ PADA IBU DARI PESERTA PROGRAM BELAJAR MATEMATIKA â€I MATHSâ€ DI TK KRISTEN TRI TUNGGAL SEMARANG - Effendy, Emmy; Ediati, Annastasia; Dewi, Endah Kumala (Faculty of Psychology, Diponegoro University, 2010)
Therefore the aim of this study was to determine whether there is a relationship between the perception of the child's mathematical ability and attitude of course I Maths in the mother of program participants learn Maths at First TK Kristen Tri Tunggal Semarang. The population of this research is the mother of program participants learn Maths at First TK Kristen Tri Tunggal Semarang. This study population of 51 mothers and 44 based on table Krecjie samples obtained with Simple Random Sampling technique. Scale used is Mother Attitude Scale of the program I Maths (26 aitems, Î± = 0,947) and Perceptions Scale for Math Ability Children (21 aitems, Î± = 0,881). Simple linear regression analysis showed the correlation coefficient = 0.674 and p = 0.000 (p <0.05). Rxy values indicate the direction of positive relations between the two variables is positive, which means that the more positive perceptions of mathematics ability, the more positive the child's mother is also the attitude toward the program I Maths, conversely the more negative perceptions of math ability children also increasingly negative attitude of mothers towards the program I Maths. The coefficient of determination of 0.455 indicates that the perception of the child's mathematical ability to contribute effectively amounted to 45.50% of maternal attitude toward the program I Maths. percentage of 54.50% can be explained by other factors such as financial, learning duration, the physical condition of children, and others.Keywords : mother, I Maths program, perception, attitude, ability in mathematics.Permalink :